Social Electricity: a case study on users perceptions in using green ICT social applications. (2016) - Kamilaris, Andreas; Pitsillides, Andreas; Fidas, Christos
Stimulated by a large number of socio-cognitive theories, suggesting that comparative feedback motivates people to adapt their behaviour according to commonly accepted behaviour and values, we developed Social Electricity, an online social application motivating users to change their electrical consumption through effective and realistic comparisons with the ones of their friends, neighbours and other users with similar characteristics. By exploiting normative social influence, the users may perceive their energy behaviour and take steps to reduce their electricity footprint. Collaborating with the local energy utility, social electricity has been deployed at a national level in Cyprus, aiming to influence citizens towards energy savings. In this paper, we present the conceptual design of the application along with analysis of results gathered through a questionnaire-based survey with 198 participants, combined with mini focus group studies, focusing on the investigation of user perceptions related to several aspects of social electricity, six months after its official release. This study provides interesting insights about the usefulness and acceptance of such large-scale, green ICT social applications, and their potential for affecting energy knowledge and awareness, encouraging users to become more sensitive about the environment and adopt pro-environmental behaviours.